Graphene-nanoscroll-based Janus bifunctional separators suppress lithium dendrites and polysulfides shuttling synchronously in high-performance lithium–sulfur batteries. Issue 17 (29th March 2022) - Zhang, Zhigang; Dong, Yanfeng; Gu, Yuefeng; Lu, Pengfei; Xue, Fangfang; Fan, Yangtao; Zhu, Zhicheng; Lin, Jun; Li, Qiuhong; Wu, Zhong-Shuai
Abstract : NGNS-PP could improve the diffusion of Li + effectively and inhibit the growth of dendrites. The Li//Li cell with NGNS-PP separator exhibited excellent cycling stability (12 000 h at 6 mA cm −2 ). Abstract : Li sulfur (Li–S) battery is regarded as one of the most promising candidates for next-generation rechargeable batteries. However, some challenging obstacles such as uncontrolled dendrites of Li metal anode and polysulfides shuttling in the sulfur cathode substantially impede the practical application. In this work, we propose a versatile strategy of fabricating graphene nanoscroll (GNS) based bifunctional Janus polypropylene (Janus PP) separators for inhibiting lithium dendrites and suppressing polysulfides shuttling toward high-performance Li–S batteries. On the anode side of the separator, nitrogen-doped GNS (NGNS) were used to protect the lithium metal. The highly uniform NGNS nanostructure facilitated electrolyte penetration and homogenous Li + flux, thus fundamentally prompting lithiation/delithiation kinetics and inhibiting the growth of Li dendrites. Due to these properties, the Li symmetrical cell with NGNS-modified PP separator (NGNS-PP) delivers an ultralow voltage hysteresis of 36 mV at 6.0 mA cm −2 after 12 000 h (65.5 mV at 10 mA cm −2 after 3400 h). On the cathode side, GNS-wrapped Co3 O4 nanoparticles (Co3 O4 @GNS) used as an interlayer on the PP separator, acting as a wonderful physical blocking and chemical catalytic layer to sufficiently mitigate the "shuttle effects" of lithium polysulfides. As a result, with the Janus PP separator, Li–S cells obtained a stable capacity of 805 mA h g −1 after 800 cycles (a capacity decay of 0.018% per cycle at 1.0C). Therefore, this proposed strategy of GNS-based Janus separators will pave a new way to rationally construct durable and efficient Li–S batteries.